ANALISIS KESIAPAN GURU BAHASA INGGRIS DALAM PEMBELAJARAN MUATAN LOKAL BAHASA INGGRIS PADA KURIKULUM MERDEKA KELAS IV SEKOLAH DASAR - Yohana, Esra; Hamidiyah, Aisyah; Setiawan, Sigit (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
One of the learning components in the Merdeka Curriculum is the inclusion of local content English lessons in public elementary schools. This study aims to describe teacher readiness in the planning, implementation, evaluation, and reflection stages of English language teaching in fourth-grade elementary classes. A descriptive qualitative method was used to examine the natural conditions and phenomena related to this topic. The subjects of this study were the principals and English teachers from two different schools: SDN Kalideres 14 Petang and SDN Pegadungan 01 Pagi. Data were collected through observation, interviews, and documentation. The data analysis technique involved data collection, data reduction, data presentation, and drawing conclusions or verification, with data validity tested using credibility, transferability, dependability, and confirmability techniques. The results show that in terms of planning readiness, teachers have carried out lesson planning that includes understanding the Merdeka Curriculum, understanding the local English content, preparing teaching tools, and preparing themselves before teaching. In terms of implementation, teachers conducted English local content lessons by applying teaching modules, using instructional tools, and managing the classroom effectively. In the aspects of evaluation and reflection, teachers prepared evaluation questions, carried out student assessments, and conducted reflections at the end of each English lesson in fourth-grade elementary classes.